Linkages To Bookkeeping Training, Business Scale, Financial Records With The Members Participation Of The Indonesian Women’s Cooperative - Sungkawati, Endang (Archives of Business Research, 2020)
Knowledge of financial analysis, especially for business activity is essential, because by having that knowledge that the members of Micro Small Enterprises (MSE) will be able to record their business finances and can distinguish business finance, business capital, and personal finance. This is happening in the agents who become a member of the Indonesia Women Cooperative. The subject, in general, do not have the knowledge and ability to record and analyze the business. So they have difficulty in fulfilling their obligations and less participates in cooperative activities. Based on this, this study aims to: know the effect of bookkeeping training and business scale on member participation moderated by financial records. The results showed that the variable financial recording is a moderating variable in influencing the bookkeeping training and business scale on the participation of members of the Indonesia Women Cooperative.